Fixed-bed adsorption studies of endocrine-disrupting compounds from water by using novel calcium-based metal-organic frameworks - Sukatis, Fahren Fazzer; Looi, Ley Juen; Lim, Hong Ngee; Abdul Rahman, Mohd Basyaruddin; Mohd Zaki, Muhammad Rozaimi; Aris, Ahmad Zaharin (Elsevier, 2024)
The presence of emerging water pollutants such as endocrine-disrupting compounds (EDCs), including 17-ethynylestradiol (EE2), bisphenol A (BPA), and perfluorooctanoic acid (PFOA), in contaminated water sources poses significant environmental and health challenges. This study aims to address this issue by investigating the efficiency of novel calcium-based metal-organic frameworks, known as mixed-linker calcium-based metal-organic frameworks (Ca-MIX), in adsorbing these endocrine-disrupting compounds. This study analyzed the influence of influent concentration, bed height, and flow rate on pollutant removal, with bed height emerging as a crucial factor. From the breakthrough curves, it was determined that the column maximum adsorption capacities followed the order of 17-ethynylestradiol (101.52 μg/g; 40%) > bisphenol A (99.07 μg/g; 39%) > perfluorooctanoic acid (81.28 μg/g; 32%). Three models were used to predict the adsorption process, with the Yan model outperforming the other models. This suggests the potential of mixed-linker calcium-based metal-organic frameworks for removing endocrine-disrupting compounds from water, using the Yan model as an effective predictor. Overall, this study provides valuable insights for the development of effective water treatment methods using mixed-linker calcium-based metal-organic frameworks to remove endocrine-disrupting compounds from contaminated water sources.